Otimização do uso de produtos químicos no tratamento de água da UFLA - Freitas, Dyego Maradona Ataide de (2019)
The treatment of water for human consumption has become more and more complex and necessary due to the growth of the cities and of the releases of pollutants in the water bodies caused by the man. So that the quality of the water reaches the necessary requirements, so that they are not harmful to human health, it makes necessary a good management of the units that will carry out the process of treatment of the water to make it potable The Federal University of Lavras owns a station (ETA), where a study was carried out on the application of the chemical inputs used in this unit. Therefore, the objective of the present work was to improve the use of these inputs, in accordance with the current legislation, in order to provide water to the UFLA community with good quality. The study was carried out in two stages, the first with jar test in samples with variations of pH and turbidity, to evaluate the application of coagulant and alkalinizer in several situations in order to optimize the coagulation and flocculation processes, was also evaluated the actual efficiency of the use of oxidant as pre-treatment in the removal of iron and organic matter and the study of the potential of trihalomethanes generation.